Evaluation of image quality of wideband single‐shot late gadolinium‐enhancement MRI in patients with a cardiac implantable electronic device. (13th November 2020) - Schwartz, Sarah M.; Pathrose, Ashitha; Serhal, Ali M.; Ragin, Ann B.; Charron, Jessica; Knight, Bradley P.; Passman, Rod S.; Avery, Ryan J.; Kim, Daniel
Abstract: Introduction: While wideband segmented, breath‐hold late gadolinium‐enhancement (LGE) cardiovascular magnetic resonance (CMR) has been shown to suppress image artifacts associated with cardiac‐implanted electronic devices (CIEDs), it may produce image artifacts in patients with arrhythmia and/or dyspnea. Single‐shot LGE is capable of suppressing said artifacts. We sought to compare the performance of wideband single‐shot free‐breathing LGE against the standard and wideband‐segmented LGEs in CIED patients. Methods and Results: We retrospectively identified all 54 consecutive patients (mean age: 61 ± 15 years; 31% females) with CIED who had undergone CMR with standard segmented, wideband segmented, and/or wideband single‐shot LGE sequences as part of quality assurance for determining best clinical practice at 1.5 T. Two raters independently graded the conspicuity of myocardial scar or normal myocardium and the presence of device artifact level on a 5‐point Likert scale (1: worst; 3: acceptable; 5: best). Summed visual score (SVS) was calculated as the sum of conspicuity and artifact scores (SVS ≥ 6 defined as diagnostically interpretable). Median conspicuity and artifact scores were significantly better for wideband single‐shot LGE ( F = 24.2, p < .001) and wideband‐segmented LGE ( F = 20.6, p < .001) compared to standard‐segmented LGE. Among evaluated myocardial segments, 72% were deemed diagnostically interpretable—defined as SVS ≥ 6—for standard‐segmented LGE, 89% were deemed diagnostically interpretable for wideband‐segmented LGE, and 94% segments were deemed diagnostically interpretable for wideband single‐shot LGE. Conclusions: Wideband single‐shot LGE and wideband‐segmented LGE produced similarly improved image quality compared to standard LGE.